Partitioning of platinum-group elements between metal and sulphide melt in the Cu-S and Ni-S systems - Merkle, R.K.W. (Roland Karl Willi), 1954- (University of Pretoria, 2013)
Dissertation (MSc (Applied Mineralogy))--University of Pretoria, 2005.